Labour transitions and inequality: occupational mobility, labour informality, and wages in Germany, Spain, Italy, Poland, and Argentina (2022–2023) - Salvia, Agustín (2025)
Fil: Salvia, Agustín. Pontificia Universidad Católica Argentina. Observatorio de la Deuda Social Argentina; Argentina